Medication Administration Error Reporting and Associated Factors among Nurses Working in Public Hospitals, Ethiopia: A Cross-Sectional Study - Kokebie kefelegn Asefa; Deguale Dagne; Wassie Negash Mekonnen (Nursing Research and Practice)
Background. Medication administration error is one of the most common errors that occur when a discrepancy occurs between the drugs received by the patient and the drug intended by the prescriber. A lot of studies were conducted on medication administration error. But there were a few studies on whether those medication administration errors are reported or not among nurses in Ethiopia. So this study is aimed at assessing the magnitude of medication administration error reporting and the associated factors among nurses. Objectives. To assess the magnitude of reported medication administration error and associated factors among nurses working in public hospitals, Ethiopia. Methods. An institutional-based cross-sectional study design was employed from March to April 2019. Simple random sampling technique was used. A structured self-administered questionnaire was used to collect the data. Data were entered using EpiData version 3.1 and descriptive analysis, bivariate, and multivariate logistic regression analyses were carried out using SPSS version 21 software. Results. The magnitude of medication administration error reporting was found to be 37.9%. Being female [adjusted odds ratio (AOR) = 2.91; confidence interval (CI) (1.45–5.85)]; belief that errors should not be reported [AOR = .3; CI (.15–.61)]; having work experience of greater than 15 years [AOR = 3.4; CI (1.11–13.85)]; having bachelor science degree [AOR = 3.27; CI (1.61–6.66)]; and caring for greater than 10 patients [(AOR = .4; CI (.16–.96)] were factors associated with nurses medication administration error reporting. Conclusion. The magnitude of medication administration error reporting among nurses was found to be low. To increase medication administration error reporting, efforts should be made to change the attitude of nurses on the belief that errors should be reported, retaining staffs that have longer experience, upgrading staffs educational status, and limiting the number of patients cared by a single nurse.